Game design framework: a pilot study on users’ perceptions - Ahmad, Ibrahim; Jaafar, Azizah (Springer-Verlag Berlin Heidelberg, 2011)
Study on computer game design has a lot been carried out. Many researchers stated that the design of the computer game is able to influence users’ emotions that play the game. This working paper tries to discuss on framework for the design of a computer game. Analyze and repossession that explained is the pilot study on respondent view on the type of game design that they wanted.